Preparation method of graphene adsorption pad applied to treatment of industrial sewage

CN118767870BActive Publication Date: 2026-10-09SHENYANG LIGONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410800998.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2026-10-09
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

大量的文献报道了石墨烯通常以气凝胶的形式来进行水处理,合成方法是采用水热法或溶剂热法进行合成的,虽然取得良好的效果,但石墨烯气凝胶的体积无法做大,这主要是因为高温反应釜的体积限制以及反应过程中会产生大量气体,产生巨大的气压,从而带来安全隐患造成的结果

Benefits of technology

[0012] The graphene adsorption pads prepared using the method of this invention can be applied in wastewater treatment, heat dissipation, and industrial catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118767870B_ABST
    Figure CN118767870B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of graphene material, and discloses a preparation method of a graphene adsorption pad applied to treating industrial sewage. A graphene oxide solution is prepared as a precursor spinning solution and is loaded into an injector of an electrostatic spinning device, a voltage is applied to perform electrostatic spinning, and a semi-finished product fiber is obtained. The semi-finished product fiber is placed into a vacuum chamber copper crucible of an electron beam physical vapor deposition device in 20-30 strands, and heat reduction and pore forming treatment are sequentially performed by using an electron beam, so that graphene fibers are obtained. The graphene fibers after pore forming in 5-10 strands are twisted into one strand and are wound on a winding drum to prepare graphene strand yarn, and weaving is performed by using a loom, the warp yarn and the weft yarn both adopt the graphene strand yarn, and finally the graphene adsorption pad is woven. The graphene adsorption pad has a maximum adsorption capacity of 486.5 mg / g for methylene blue dye, and a maximum adsorption capacity of 263.3 mg / g for hexavalent chromium ions, and has a good effect of adsorbing industrial pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of graphene materials technology, and in particular to a method for preparing a graphene adsorption pad for treating industrial wastewater. Background Technology

[0002] Graphene is a type of carbon atom arranged in sp... 2 Two-dimensional carbon nanomaterials with a hexagonal honeycomb lattice composed of hybrid orbitals. They possess a large specific surface area (2630 m²). 2 Graphene ( / g) can be applied in water treatment to adsorb harmful substances such as heavy metal ions, organic dyes, organic oil stains, and antibiotics. Compared to expensive fullerenes and carbon nanotubes, graphene is inexpensive and readily available. Numerous studies have reported that graphene is typically used for water treatment in the form of aerogels, synthesized using hydrothermal or solvothermal methods. While these methods have yielded good results, the volume of graphene aerogels cannot be increased significantly. This is mainly due to the volume limitations of high-temperature reactors and the large amount of gas generated during the reaction, resulting in enormous pressure and potential safety hazards. Furthermore, even using tens to hundreds of graphene aerogels cannot completely treat large quantities of industrial wastewater, hindering its practical application in industrial wastewater treatment. However, if graphene were made into fibers or yarns and woven into fabrics or mats, it could be used to treat large quantities of industrial wastewater. Textile technology allows for the weaving of large-area fabrics, and the size of graphene mats can be customized according to the volume of wastewater to be treated. When in use, it can be cast into the water like a fishing net, and then the graphene pad can be bound with stones. Thanks to the ultra-high strength and ultra-high toughness of graphene, it can resist the impact of water flow and adsorb pollutants onto the graphene pad. After use, the pollutants can be recycled and cleaned. The pad can be reused, achieving a very good sewage treatment effect. Summary of the Invention

[0003] The purpose of this invention is to solve the problems of the prior art and provide a method for preparing graphene adsorption pads for treating industrial wastewater. The process is simple and easy to scale up. The graphene adsorption pads prepared by this invention can adsorb pollutants such as organic dyes and heavy metal ions, and have good adsorption effect in the field of water treatment.

[0004] To achieve the above objectives, the technical solution of the present invention is as follows:

[0005] A method for preparing a graphene adsorption pad for treating industrial wastewater includes the following steps:

[0006] Step (1): Prepare a concentration of 2–20 mg / mL -1Graphene oxide solution; the graphene oxide solution is used as a precursor spinning solution and loaded into a syringe in an electrospinning device, and a voltage is applied to perform electrospinning to obtain graphene oxide fibers.

[0007] Step (2): 20 to 30 strands of graphene oxide fiber are placed in a copper crucible in the vacuum chamber of an electron beam physical vapor deposition apparatus, and thermal reduction and pore-forming treatment are performed sequentially by electron beam to obtain graphene fiber.

[0008] Step (3): Using a textile fiber interlacing device, twist 5 to 10 strands of perforated graphene fibers into one strand and wind it onto a bobbin to make graphene strands. Then, use a loom to weave the fabric. Both the warp and weft yarns are made of the graphene strands. Finally, weave the graphene adsorption pad.

[0009] The graphene oxide in the graphene oxide solution is produced by chemical oxidation or electrochemical oxidation.

[0010] The voltage applied during electrospinning is in the range of 45–55 kV.

[0011] The thermal reduction process parameters for graphene fibers are: voltage 15–25 kV, beam current 100–200 mA, vapor particle incident angle 30–60°, processing time 10–30 min, and vacuum degree 5 × 10⁻⁶. -6 ~7×10 -6 Pa; the process parameters for pore formation were voltage 6-12kV, beam current 50-80mA, vapor particle incident angle 30-60°, and processing time 20-40min; the thickness of the graphene fiber obtained after thermal reduction and pore formation was 10-50μm.

[0012] The graphene adsorption pads prepared using the method of this invention can be applied in wastewater treatment, heat dissipation, and industrial catalysts.

[0013] This invention employs electrospinning to prepare graphene fibers, which are then woven into graphene mats. These mats are applied in water treatment to adsorb pollutants such as organic oil and heavy metal ions. This overcomes the shortcomings of existing graphene aerogel technologies, making the graphene mats of this invention suitable for practical applications in industrial wastewater treatment. Furthermore, a key feature of this invention is the use of an electron beam in an electron beam physical vapor phase apparatus to pre-treat the semi-finished graphene oxide fibers in a copper crucible with a thermal reduction treatment. This removes oxide groups and impurities from the graphene oxide, resulting in high-quality graphene fibers. This method is superior to traditional thermal reduction treatments using tube furnaces or muffle furnaces. Next, energy parameters are lowered to create pores in the graphene. Due to the high power of the electron gun in the apparatus, the processing range is large, enabling the formation of micropores over a wide area. The principle of electron beam pore formation is as follows: reducing the energy of the electron beam causes the beam spot to be discretely distributed, so that the energy acts on different positions on the surface and evaporates to form micropores. Conversely, increasing the energy makes the beam spot more concentrated, which makes it easier for a large number of carbon atoms on the graphene surface to volatilize, thus failing to achieve pore formation in graphene fibers.

[0014] The beneficial effects of this invention are as follows: This invention relates to a method for preparing a graphene adsorption pad for treating industrial wastewater. Graphene fibers are prepared using electrospinning, and then the fibers are woven into a graphene pad. This pad product is applied in the water treatment field and can adsorb pollutants such as organic dyes and heavy metal ions. It overcomes the shortcomings of existing graphene aerogel technology, making the graphene pad of this invention suitable for practical applications in wastewater treatment. The maximum adsorption capacity of the graphene adsorption pad of this invention for methylene blue dye is 486.5 mg / g, and the maximum adsorption capacity for hexavalent chromium ions is 263.3 mg / g, demonstrating excellent adsorption performance for industrial pollutants. Attached Figure Description

[0015] Figure 1 This is a SEM image showing the microstructure of the graphene fibers of this invention.

[0016] Figure 2 SEM image of the microstructure of the graphene adsorption pad of the present invention.

[0017] Figure 3 The graph shows a comparison of the adsorption performance of methylene blue dye in Examples 1-3 and Comparative Examples 1-3.

[0018] Figure 4 The graph shows a comparison of the adsorption performance of hexavalent chromium ions in Examples 1-3 and Comparative Examples 1-3. Detailed Implementation

[0019] The present invention will be further described below with reference to specific embodiments.

[0020] Example 1

[0021] A method for preparing a graphene adsorption pad for treating industrial wastewater, the specific preparation process of which is as follows:

[0022] Step (1): Prepare a solution with a concentration of 2 mg / mL -1 Graphene oxide solution; the graphene oxide solution is used as a precursor spinning solution and loaded into a syringe in an electrospinning device, and a voltage is applied to perform electrospinning to obtain graphene oxide fibers.

[0023] Step (2): 20 strands of graphene oxide fiber are placed in a copper crucible in the vacuum chamber of an electron beam physical vapor deposition apparatus. The graphene fiber is then subjected to thermal reduction and pore-forming treatment by electron beam in sequence.

[0024] Step (3): Using a textile fiber interlacing device, twist the five perforated graphene fibers into one strand and wind them onto a bobbin to make graphene strands. Then, use a loom to weave the fabric. Both the warp and weft yarns are made of the graphene strands. Finally, weave the graphene adsorption pad.

[0025] Preferably, the graphene oxide in the graphene oxide solution is produced by chemical oxidation or electrochemical oxidation.

[0026] Preferably, the applied voltage range during electrospinning is 45kV.

[0027] Preferably, the thermal reduction process parameters for the graphene fiber are: voltage 15kV, beam current 100mA, vapor particle incident angle 30°, processing time 10min, and vacuum degree 5×10⁻⁶. -6 Pa; the process parameters for the pore-forming treatment are: voltage 6kV, beam current 50mA, vapor particle incident angle 30°, treatment time 20min, and electron beam is a continuous electron beam; the thickness of the graphene fiber obtained after thermal reduction and pore-forming treatment is 10μm.

[0028] Preferably, the prepared graphene adsorption pad can be applied to wastewater treatment, heat dissipation, and industrial catalysts.

[0029] Adsorption performance tests showed that the maximum adsorption capacity for methylene blue dye was 456.5 mg / g, and the maximum adsorption capacity for hexavalent chromium ions was 237.1 mg / g.

[0030] Example 2

[0031] A method for preparing a graphene adsorption pad for treating industrial wastewater, the specific preparation process of which is as follows:

[0032] Step (1): Prepare a solution with a concentration of 11 mg·mL -1Graphene oxide solution; the graphene oxide solution is used as a precursor spinning solution and loaded into a syringe in an electrospinning device, and a voltage is applied to perform electrospinning to obtain graphene oxide fibers.

[0033] Step (2): 25 strands of graphene oxide fiber are placed into a copper crucible in the vacuum chamber of an electron beam physical vapor deposition apparatus. The graphene fiber is then subjected to thermal reduction and pore-forming treatment by electron beam in sequence.

[0034] Step (3): Using a textile fiber interlacing device, the 7 perforated graphene fibers are twisted into one strand and wound onto a bobbin to make graphene strands. Then, a weaving machine is used to weave the fabric, with both the warp and weft yarns made of the graphene strands. Finally, a graphene adsorption pad is woven.

[0035] Preferably, the graphene oxide in the graphene oxide solution is produced by chemical oxidation or electrochemical oxidation.

[0036] Preferably, the applied voltage range during electrospinning is 50kV.

[0037] Preferably, the thermal reduction process parameters for the graphene fiber are: voltage 20kV, beam current 150mA, vapor particle incident angle 45°, processing time 20min, and vacuum degree 6×10⁻⁶. -6 Pa; the process parameters for the pore-forming treatment are: voltage 9kV, beam current 65mA, vapor particle incident angle 45°, and treatment time 30min; the thickness of the graphene fiber obtained after thermal reduction and pore-forming treatment is 35μm.

[0038] Preferably, the prepared graphene adsorption pad can be applied to wastewater treatment, heat dissipation, and industrial catalysts.

[0039] Adsorption performance tests showed that the maximum adsorption capacity for methylene blue dye was 486.5 mg / g, and the maximum adsorption capacity for hexavalent chromium ions was 263.3 mg / g.

[0040] Example 3

[0041] A method for preparing a graphene adsorption pad for treating industrial wastewater, the specific preparation process of which is as follows:

[0042] Step (1): Prepare a solution with a concentration of 20 mg / mL. -1 Graphene oxide solution; the graphene oxide solution is used as a precursor spinning solution and loaded into a syringe in an electrospinning device, and a voltage is applied to perform electrospinning to obtain graphene oxide fibers.

[0043] Step (2): 30 strands of graphene oxide fibers are placed into a copper crucible in the vacuum chamber of an electron beam physical vapor deposition apparatus, and thermal reduction and pore-forming treatment are performed in sequence to obtain graphene fibers.

[0044] Step (3): Using a textile fiber interlacing device, twist 10 perforated graphene fibers into one strand and wind them onto a bobbin to make graphene strands. Then, use a loom to weave the fabric. Both the warp and weft yarns are made of the graphene strands. Finally, weave a graphene adsorption pad.

[0045] Preferably, the graphene oxide in the graphene oxide solution is produced by chemical oxidation or electrochemical oxidation.

[0046] Preferably, the applied voltage range during electrospinning is 55kV.

[0047] Preferably, the thermal reduction process parameters for the graphene fiber are: voltage 25kV, beam current 200mA, vapor particle incident angle 60°, processing time 30min, and vacuum degree 7×10⁻⁶. -6 Pa; the process parameters for the pore-forming treatment are: voltage 12kV, beam current 80mA, vapor particle incident angle 60°, and treatment time 40min; the thickness of the graphene fiber obtained after thermal reduction and pore-forming treatment is 50μm.

[0048] Preferably, the prepared graphene adsorption pad can be applied to wastewater treatment, heat dissipation, and industrial catalysts.

[0049] Adsorption performance tests showed that the maximum adsorption capacity for methylene blue dye was 467.3 mg / g, and the maximum adsorption capacity for hexavalent chromium ions was 251.9 mg / g.

[0050] Comparative Example 1:

[0051] Comparative Example 1 uses a hydrothermal method to synthesize graphene aerogels from graphene oxide. First, a 10 mg / mL solution is prepared. -1 A graphene oxide solution was prepared by placing the graphene oxide solution into a high-temperature reactor, adding hydrazine hydrate as a reducing agent, and hydrothermating at 180°C for 12 hours to produce graphene aerogel.

[0052] Adsorption performance tests showed that the maximum adsorption capacity for methylene blue dye was 393.8 mg / g, and the maximum adsorption capacity for hexavalent chromium ions was 203.1 mg / g.

[0053] The difference between Comparative Example 2 and Example 2 is that the graphene oxide fiber heat treatment is performed using a traditional muffle furnace with heat treatment parameters of 550°C and 3 hours, using argon as the inert protective gas in the muffle furnace. The subsequent pore-forming process is still completed using electron beam vapor deposition equipment, and the process is unchanged from that of Example 2, finally producing a graphene adsorption pad.

[0054] The adsorption performance test of Comparative Example 2 showed that the maximum adsorption capacity for methylene blue dye was 456.7 mg / g, and the maximum adsorption capacity for hexavalent chromium ions was 241.2 mg / g. The reason why Example 2 showed better adsorption performance than Comparative Example 2 is that the electron beam can not only remove oxygen-containing groups, but also remove impurities such as manganese ions and alkali metal ions from the graphene oxide fibers, causing the impurities to volatilize and improving the purity of the graphene fibers. Impurities are also one of the factors affecting the adsorption performance of the product.

[0055] The difference between Comparative Example 3 and Example 2 lies in the electron beam aperture formation process parameters. The aperture formation process parameters for Comparative Example 3 are: voltage 20kV, beam current 100mA, vapor particle incident angle 45°, and processing time 20min. The remaining processes and parameters are consistent with those of Example 2.

[0056] The adsorption performance test of Comparative Example 3 showed that the maximum adsorption capacity for methylene blue dye was 301.6 mg / g, and the maximum adsorption capacity for hexavalent chromium ions was 154.9 mg / g. When the energy parameters (voltage and beam current) for pore formation exceed the normal range, a large amount of carbon atoms on the graphene fiber surface will evaporate, failing to achieve the pore-forming effect. Therefore, the adsorption performance of Comparative Example 3 is far inferior to that of Example 2.

[0057] Adsorption performance test:

[0058] Methylene blue dye and potassium dichromate were selected as the adsorption performance research objects. A 9L solution of methylene blue dye and potassium dichromate, both with a concentration of 1000 mg / L, was prepared beforehand. The adsorption performance of the graphene pad was tested in a 10L glass bath with mechanical stirring at 900 rpm to simulate the impact of water flow on the graphene adsorption pad. The absorbance of the solution was measured using a Hitachi U-3900 UV spectrophotometer. The concentration of the solution after adsorption was obtained using the methylene blue dye absorbance A-concentration C relationship (A = 0.206C - 0.005) and the hexavalent chromium absorbance-concentration relationship (A = 0.02C + 0.02). Finally, the maximum adsorption capacity of the graphene adsorption pad for methylene blue and hexavalent chromium was calculated.

Claims

1. A method for preparing a graphene adsorption pad for treating industrial wastewater, characterized in that, The steps include the following: Step (1): Prepare a concentration of 2~20 mg•mL -1 Graphene oxide solution; the graphene oxide solution is used as a precursor spinning solution and loaded into a syringe in an electrospinning device, and a voltage is applied to perform electrospinning to obtain graphene oxide fibers. Step (2): 20-30 strands of graphene oxide fiber are placed in a copper crucible in the vacuum chamber of an electron beam physical vapor deposition apparatus, and thermal reduction and pore-forming treatment are performed sequentially by electron beam to obtain graphene fiber. The thermal reduction process parameters for graphene fibers are: voltage 15~25kV, beam current 100~200 mA, vapor particle incident angle 30~60°, processing time 10~30 min, and vacuum degree 5×10⁻⁶. -6 ~7×10 -6 Pa; The process parameters for the pore-forming treatment are: voltage 6~12kV, beam current 50~80 mA, vapor particle incident angle 30~60°, and treatment time 20~40min; The thickness of the graphene fiber obtained after thermal reduction and pore-forming treatment is 10~50μm; Step (3): Using a textile fiber interlacing device, twist 5 to 10 strands of perforated graphene fibers into one strand and wind them onto a bobbin to make graphene strands. Then, use a loom to weave the fabric. Both the warp and weft yarns are made of the graphene strands. Finally, weave the graphene adsorption pad.

2. The method for preparing a graphene adsorption pad for treating industrial wastewater according to claim 1, characterized in that, The graphene oxide in the graphene oxide solution is produced by chemical oxidation or electrochemical oxidation.

3. A method for preparing a graphene adsorption pad for treating industrial wastewater according to claim 1 or 2, characterized in that, The voltage applied during electrospinning is in the range of 45~55kV.

4. The method for preparing a graphene adsorption pad for treating industrial wastewater according to claim 3, characterized in that, The graphene adsorption pads prepared by the above method are used in wastewater treatment.